User-defined gesture interaction for immersive VR shopping applications. Issue 7 (3rd July 2019) - Wu, Huiyue; Wang, Yu; Qiu, Jiali; Liu, Jiayi; Zhang, Xiaolong (Luke)
ABSTRACT: Gesture elicitation studies, which are a popular technology for collecting requirements and expectations by involving real users in gesture design processes, often suffer from gesture disagreement and legacy bias and may not generate optimal gestures for a target system in practice. This paper reports a research project on user-defined gestures for interacting with immersive VR shopping applications. The main contribution of this work is the proposal of a more practical method for deriving more reliable gestures than traditional gesture elicitation studies. We applied this method to a VR shopping application and obtained empirical evidence for the benefits of deriving two gestures in the a priori stage and selecting the top-two gestures in the a posteriori stage of traditional elicitation studies for each referent. We hope that this research can help lay a theoretical foundation for freehand-gesture-based user interface design and be generalised to all freehand-gesture-based applications.